Investigation on the mechanical properties of eco-friendly pervious concrete. (2021) - Muthukumar, Surya; Jai Saravanan, Amruta; Raman, Aishwarya; Shanmuga Sundaram, Madhubala; Sri Angamuthu, Sakthi
Abstract: Pervious concrete has newly undertaken to escalate for its demand. As urban areas develop, the difficulties related to runoff management have become more herculean and pervious concrete can provide a sustainable solution. Sustainable development in the field of concrete structures can be achieved by minimizing the usage of cement in concrete as it releases a large amount of CO2 leading to various hazards. The reduction of Portland cement is attained by replacing by-product from various industries. Sugarcane bagasse ash (SCBA) is obtained by burning sugarcane after the extraction of all efficient sugar from it. Disposal of the ash material causes various environmental hazards. Strength is improved by using SCBA as a supplementary material and thus makes the resultant concrete eco-friendlier and economical. The bagasse ash which passes 150 μm and retained on 90 μm similar to that of OPC is used in this study. The samples are prepared by replacement of bagasse ash with cement in different percentages and the strength parameters and permeability of concrete is tested. Six different concrete mixes with the bagasse ash replacing 0%, 5%, 10%, 15%, 20% and 25% of the OPC were prepared with water to cement ratio of 0.34 and 202.83 kg/m 3 cement content. It is found that at 15% replacement, the optimum strength is obtained. Since the aggregate sizes used for all the percentage replacements remains same, the permeability ranges from 0.2 cm/s to 0.4 cm/s.